Shortest Paths - Erciyes, K (Algebraic Graph Algorithms, 2021)
Finding the shortest shortest path between two vertices in a weighted graph has many applications. A fundamental implementation involves sending packets over shortest routes, therefore, in shortest possible time between two routers in a computer network. This so-called routing problem is commonly solved by converting a graph routing algorithm to a distributed one in the form of a network protocol to be executed by each router. We look at basic graph algorithms to find shortest paths in a weighted graph in this chapter.